Sosialisasi Alat Pelindung Diri (APD) Dalam Keselamatan Dan Kesehatan Kerja (K3) Untuk Meningkatkan Pemahaman Siswa Di SMK Negeri 2 Bandar Lampung - Amelia Oktvia; Rina Febrina; Dimas Ardiansyah; Annisa Vica Aulia; Arini Lutfia Laili; Adriyansyah (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
Occupational Safety and Health (OSH) is an important aspect in creating a safe and healthy work environment, especially in vocational education which involves many practical activities. One of the efforts in implementing OSH is the proper and disciplined use of Personal Protective Equipment (PPE). However, students' awareness regarding PPE usage is still relatively low. This community service activity aimed to improve students’ understanding of the importance of PPE usage in the implementation of OSH at SMK Negeri 2 Bandar Lampung. The implementation methods included pre-test, material presentation, PPE usage demonstration, PPE practice session, discussion and question-answer session, and post-test. Participants consisted of eleventh-grade students from DPIB and Geomatics classes. The results showed an increase in participants’ understanding, indicated by the improvement in the average pre-test score from 88.78 to 97.11 in the post-test. In addition, participants showed high enthusiasm during the activity. This activity successfully improved students’ understanding and awareness regarding the importance of PPE usage to support occupational safety both in school and future workplaces.